MINE DRAINAGE FACILITY PLANNING AT OUT-PIT DUMP C1 SITE BINUNGAN MINE OPERATION 2 BLOK 8 PT BERAU COAL, EAST KALIMANTAN - Clara Chika Giri Asta P, Putu
In open-pit mining, the overburden material needs to be excavated or blasted to a certain depth. The material will be transported to the disposal area according to the planned progress plan. When there is heavy rain, the disposal material will be eroded due to its characteristic as a loose material. Therefore, it is necessary to design drainage facilities that can reduce the impact of erosion so that the water quality meets the effluent standards in the post-mining period.